2021
DOI: 10.15575/ak.v8i1.11885
|View full text |Cite
|
Sign up to set email alerts
|

Uji Aktivitas Fotokatalis Senyawa Aurivillius Lapis EmpaT SrBi4Ti4O15 dalam Mendegradasi Rhodamine-B

Abstract: Senyawa berstruktur Aurivillius dilaporkan mempunyai potensi untuk digunakan sebagai material fotokatalis. Dalam penelitian ini dikaji kemampuan aktivitas fotokatalis senyawa Aurivillius lapis empat SrBi4Ti4O15 dalam mendegradasi senyawa Rhodamine-B. Senyawa uji SrBi4Ti4O15 disintesis melalui metode lelehan garam campuran Na2SO4/K2SO4. Difraktogram menunjukkan bahwa senyawa SrBi4Ti4O15 telah berhasil disintesis dan tidak ditemukan fasa pengotor. Hasil refinement difraktogram dengan metode Rietvield diketahui b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The crystal structure of calcium is based on the results of diffractogram analysis with HighScore Plus version 3.0.5 (Luthfiah et al, 2021). The success rate of diffractogram analysis in the Highscore Plus is indicated by the low value of the Goodness of Fit (GoF) parameter (Toby, 2006) after the refinement process using the Rietveld method (Haikal & Prasetyo, 2021). The particle size analysis of calcium crystals (D) was based on the results of the diffractogram with the Scherrer equation (Usman et al, 2020) in equation 2 below: with K = 0.9 (Scherrer's constant); λ = 0.154060 nm (wavelength of light source); B = FWHM (Full Width at Half Maximum) (radians); θ = Peak position (radians).…”
Section: Calcium Extractionmentioning
confidence: 99%
“…The crystal structure of calcium is based on the results of diffractogram analysis with HighScore Plus version 3.0.5 (Luthfiah et al, 2021). The success rate of diffractogram analysis in the Highscore Plus is indicated by the low value of the Goodness of Fit (GoF) parameter (Toby, 2006) after the refinement process using the Rietveld method (Haikal & Prasetyo, 2021). The particle size analysis of calcium crystals (D) was based on the results of the diffractogram with the Scherrer equation (Usman et al, 2020) in equation 2 below: with K = 0.9 (Scherrer's constant); λ = 0.154060 nm (wavelength of light source); B = FWHM (Full Width at Half Maximum) (radians); θ = Peak position (radians).…”
Section: Calcium Extractionmentioning
confidence: 99%
“…SrBi4Ti4O15 is a four-layer Aurivillius compound with a band gap energy of 3.0 eV that has better photocatalytic activity in reducing CO2 gas than Bi4Ti3O12, TiO2, and BiOBr (Tu et al, 2019). In addition, Haikal and Prasetyo (2021) also reported that SrBi4Ti4O15 can degrade rhodamine B by 41.10% in 120 minutes.…”
Section: Introductionmentioning
confidence: 99%
“…One class of compounds reported to be used as photocatalyst materials are is Aurivillius structure. SrBi 4 Ti 4 O 15 compound is one of the four Aurivillius structure family that can be used as a photocatalyst with a band gap energy of 3.02 eV (410 nm) [3]. Decreasing the band gap energy will benefit its utilization as a photocatalyst material.…”
Section: Introductionmentioning
confidence: 99%